Macronutrient Content of Seaweed Noodles (Eucheuma cottonii) and Their Use as a Learning Medium - Ningsih, Diva Rizky Aria; Laenggeng, Abd. Hakim; Nurdin, Musdalifah; Lilies; Ashari, Abdul; Masrianih (Bioscientist : Jurnal Ilmiah Biologi, 2026)
This study aimed to analyze the macronutrient composition of seaweed noodles (Eucheuma cottonii) formulated with different levels of seaweed flour substitution and to develop the research findings into a poster-based learning medium. A laboratory experiment was conducted using a one-factor completely randomized design (CRD) comprising four treatments: P0 (100% wheat flour:0% seaweed flour), P1 (90%:10%), P2 (80%:20%), and P3 (70%:30%), with three replicates per treatment. Carbohydrate, protein, and fat contents were determined using the Anthrone, Biuret, and Soxhlet methods, respectively. Macronutrient data were analyzed using one-way analysis of variance (ANOVA) at a 5% significance level, followed by the least significant difference (LSD) test. Seaweed flour substitution significantly affected the carbohydrate, protein, and fat contents of the noodles. The carbohydrate contents of P0, P1, P2, and P3 were 56.278%, 71.631%, 68.402%, and 65.490%, respectively. The corresponding protein contents were 4.355%, 7.441%, 6.458%, and 5.337%, while the fat contents were 1.117%, 1.262%, 1.097%, and 0.896%, respectively. Among the tested formulations, P1 exhibited the highest carbohydrate and protein contents. The poster-based learning medium received feasibility scores of 85% from the content expert, 85% from the design expert, 85% from the media expert, and 90% from the student participants, yielding an overall mean score of 86.25% and placing it in the highly feasible category. These findings demonstrate that E. cottonii substitution affects the macronutrient profile of noodles and that the resulting research findings can be effectively developed into a feasible research-based learning medium.